2022
DOI: 10.1167/tvst.11.2.29
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 16S rDNA Amplicon Sequencing With the Culture Method for Diagnosing Causative Pathogens in Bacterial Corneal Infections

Abstract: Purpose The purpose of this study was to explore if 16S rDNA amplicon sequencing can improve the conventional diagnosis of causative pathogens for bacterial corneal infection. Methods Corneal scraping and conjunctiva and eyelid margin swab samples from infected eyes of patients diagnosed with “bacterial corneal infection” and conjunctiva and eyelid margin swab samples from a random eye of healthy participants were collected. Each swab was used for both aerobic and anaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In addition, NGS can result in non-selective amplifications of the RNA / DNA of the causative organisms and normal ocular surface commensals, which will require special bioinformatic consideration and analysis (hence the need for additional resources, facilities and expertise). Another issue that has been highlighted is that NGS may produce inconsistent results to the conventional culture methods, which may complicate the clinical findings and decision making in IK (An et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NGS can result in non-selective amplifications of the RNA / DNA of the causative organisms and normal ocular surface commensals, which will require special bioinformatic consideration and analysis (hence the need for additional resources, facilities and expertise). Another issue that has been highlighted is that NGS may produce inconsistent results to the conventional culture methods, which may complicate the clinical findings and decision making in IK (An et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, multiplex PCR or metagenomic next generation sequencing may also further improve the diagnosis of IK, though its routine use in clinic is currently limited by the cost and the availability of technical expertise and resources. [44][45][46][47][48] However, it has also been reported that by adopting an intensive antibiotic treatment regime for sight threatening IK, the clinical outcome of culture positive and culture negative cases was not significantly different. 4,49 Our study observed a moderate diagnostic yield in both culture and PCR methods (ranged 40-50%), which might be related to the inclusion of less severe infection cases (~60% of the cases have an infiltrate size of <3mm).…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rDNA sequencing followed previously described protocols [ 36 , 37 ]. The V3-V4 region of 16S rDNA was cloned and prepared for high-throughput sequencing on an Illumina HiSeq 2500 platform in Novogene Co., Ltd. (Novogene, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%